2017
DOI: 10.3389/fpsyg.2017.01538
|View full text |Cite
|
Sign up to set email alerts
|

A Tri-network Model of Human Semantic Processing

Abstract: Humans process the meaning of the world via both verbal and nonverbal modalities. It has been established that widely distributed cortical regions are involved in semantic processing, yet the global wiring pattern of this brain system has not been considered in the current neurocognitive semantic models. We review evidence from the brain-network perspective, which shows that the semantic system is topologically segregated into three brain modules. Revisiting previous region-based evidence in light of these new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
47
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 129 publications
(212 reference statements)
10
47
0
2
Order By: Relevance
“…These dimensions also tend to be associated with different large-scale brain networks, as shown here and previously (Jackson et al, 2016). The clustering of these different semantic dimensions may make the ATL one of the ideal regions to represent a multidimensional semantic space in a population-coding fashion by pooling multiple semantic and linguistic dimensions (Xu et al, 2017). Future studies should try to understand the relationships between the neuronal structures of these distinct ATL subregions and their corresponding semantic dimensions, as well as the regions outside the ATL for a given semantic dimension.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…These dimensions also tend to be associated with different large-scale brain networks, as shown here and previously (Jackson et al, 2016). The clustering of these different semantic dimensions may make the ATL one of the ideal regions to represent a multidimensional semantic space in a population-coding fashion by pooling multiple semantic and linguistic dimensions (Xu et al, 2017). Future studies should try to understand the relationships between the neuronal structures of these distinct ATL subregions and their corresponding semantic dimensions, as well as the regions outside the ATL for a given semantic dimension.…”
Section: Discussionsupporting
confidence: 57%
“…In addition to the three dimensions shown here, previous studies also reported the involvement of the ATL in artifacts (Bi et al, 2011), unique entities (Ross & Olson, 2012;Wang et al, 2016), concrete words in general Striem-Amit et al, 2018), and object perceptibility (Striem-Amit et al, 2018; for a review, see Lambon Ralph et al, 2017). The clustering of these different semantic dimensions may make the ATL one of the ideal regions to represent a multidimensional semantic space in a population-coding fashion by pooling multiple semantic and linguistic dimensions (Xu et al, 2017). The clustering of these different semantic dimensions may make the ATL one of the ideal regions to represent a multidimensional semantic space in a population-coding fashion by pooling multiple semantic and linguistic dimensions (Xu et al, 2017).…”
Section: Discussionsupporting
confidence: 51%
“…Another semantic model considered three functional networks as the basis of semantic processing, comprising (1) a perisylvian "language-supported system" (partially overlapping with the core language network as defined here), (2) a "multimodal experiential system" also addressed as the "default mode network" integrating experience-based knowledge across multiple modalities (see below), and (3) a left-dominant frontoparietal network as a semantic control system (Xu et al, 2017). These three networks are linked together in hub regions, comprising the anterior temporal lobe, posterior middle temporal gyrus, posterior intraparietal sulcus, angular gyrus, and parts of superior and middle frontal gyrus.…”
Section: The Semantic Systemmentioning
confidence: 99%
“…Although object knowledge can be acquired both through sensory experience (seeing red roses) and through language description (e.g., being told by others that roses are “red”), one prominent theory assumes that such knowledge is stored in sensory association cortices, derived from sensory experiences (i.e., seeing the colors of roses) (Barsalou et al, 2003; Martin, 2016; Simmons et al, 2007). The alternative possibility is that even sensory-derived knowledge is also represented at an abstract conceptual level distinct from sensory representations (Leshinskaya and Caramazza, 2016; Mahon and Caramazza, 2008; Shallice, 1988, 1987; Wang et al, 2018; Xu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%